The principle of legality as a minimum requirement to legitimize the criminal power of the State - Cristóbal Támara, Teodorico (2020)
This article analyses the principle of legality and argues that it constitutes a fundamental pillar in the theory of criminal law since it is a limit to the state’s ius puniendi. Likewise, this principle is manifested in the sub principles of written law, strict law and the prior law, which must reside in every crime and offence prescribed in the criminal law. Finally, it explains how the principle of legality also limits the arbitrary application of any criminal sanction, because of its imperative nature within any constitutional state of law to be applied over the legal system. The application of this principle translates into effective legal certainty and justice that unreservedly safeguards people’s fundamental rights.